Genetic and functional insights into the fractal structure of the heart - Meyer, Hannah V.; Dawes, Timothy J. W.; Serrani, Marta; Bai, Wenjia; Tokarczuk, Paweł; Cai, Jiashen; de Marvao, Antonio; Henry, Albert; Lumbers, R. Thomas; Gierten, Jakob; Thumberger, Thomas; Wittbrodt, Joachim; et al. (Nature, 2020)
The inner surfaces of the human heart are covered by a complex network of muscular strands that is thought to be avestige of embryonic development., The function of these trabeculae in adults and their genetic architecture are unknown. To investigate this, we performed a genome-wide association study using fractal analysis of trabecular morphology as an image-derived phenotype in 18,096 UK Biobank participants. We identified 16 significant loci containing genes associated with haemodynamic phenotypes and regulation of cytoskeletal arborisation., Using biomechanical simulations and human observational data, we demonstrate that trabecular morphology is an important determinant of cardiac performance. Through genetic association studies with cardiac disease phenotypes and Mendelian randomisation, we find a causal relationship between trabecular morphology and cardiovascular disease risk. These findings suggest an unexpected role for myocardial trabeculae in the function of the adult heart, identify conserved pathways that regulate structural complexity, and reveal their influence on susceptibility to disease.